Blooms of a key grazer in the Southern Ocean – An individual-based model of Salpa thompsoni. (June 2020) - Groeneveld, Jürgen; Berger, Uta; Henschke, Natasha; Pakhomov, Evgeny A.; Reiss, Christian S.; Meyer, Bettina
Highlights: An individual-based model of Salpa thompsoni has been developed. The model reproduces observed patterns at the individual and population level. In the model large salp blooms require a founding population in early spring. Abstract: The Southern Ocean near the Western Antarctic Peninsula (WAP) is strongly affected by climate change resulting in warmer air temperature, accompanied with reduced sea ice coverage, increased sea water temperature and potential changes in the abundances of two key grazer species Salpa thompsoni (salp) and Euphausia superba (Antarctic krill). While salp abundance is hypothesized to increase, krill abundance is hypothesized to decline with dramatic consequences for the entire food web of the Southern Ocean. A better understanding of the biotic interaction between krill and salps and their population dynamics is thus crucial. However, the life cycle of salps is complicated and barely understood. Therefore, we have developed an individual-based model describing the whole life cycle to better understand the population dynamics of salps and the conditions for blooms. The model has been used to explore if and under what conditions the empirical pattern of large variability in observed salp abundances at the WAP, generated by the long-term data of the US Antarctic Marine Living Resources Program (AMLR) can emerge from a small seeding population. The model reproduced this empirical pattern if daily growth rates of oozoids were higher than previously reported for the WAP (mean growth rate for oozoids 1 mm d −1 ) and if growth rates of blastozooids were lower (mean growth rate 0.2 mm d −1 ). The model suggests that a prerequisite for local salp blooms requires a small founding population in early spring. With climate change it has been suggested that more frequent and earlier transport of salps into the WAP or winter survival will occur. Hence, the risk of salp blooms in the WAP is likely to substantially increase. These findings highlight the importance for an improved quantitative understanding of how primary production and the southward advection of salps will be impacted by climate change.